2009
DOI: 10.1038/jcbfm.2009.97
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Role of Lactate after Cerebral Ischemia

Abstract: It is well established that lactate can be used as an energy substrate by the brain by conversion to pyruvate and a subsequent oxidation in the mitochondria. Knowing the need for readily metabolizable substrates directly after ischemia and the protective effect of lactate after excitotoxicity, the aim of this study was to investigate whether lactate administration directly after ischemia could be neuroprotective. In vitro, the addition of 4 mmol/L L-lactate to the medium of rat organotypic hippocampal slices, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
171
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 217 publications
(178 citation statements)
references
References 48 publications
5
171
1
1
Order By: Relevance
“…In addition to astrocyte-derived lactate, Boumezbeur et al (2011) and van Hall et al (2009) proposed that plasma-borne lactate may have an important role in supporting oxidative brain metabolism, suggesting that plasma-borne lactate fuels up to 60% of all cerebral metabolism and tricarboxylic acid (TCA) cycle activity even under normal physiological conditions. Consistent with this lactate-fuel hypothesis, several lines of study have also provided evidence that lactate can support energy metabolism during ischemia, which can rescue neuronal death after ischemia or under conditions of oxygen GD (Berthet et al, 2009). Recently, Rinholm et al (2011) reported that lactate can support axonal function in white matter under conditions of energy deprivation and that exogenous L-lactate can support oligodendrocyte development and myelination.…”
Section: Introductionmentioning
confidence: 71%
“…In addition to astrocyte-derived lactate, Boumezbeur et al (2011) and van Hall et al (2009) proposed that plasma-borne lactate may have an important role in supporting oxidative brain metabolism, suggesting that plasma-borne lactate fuels up to 60% of all cerebral metabolism and tricarboxylic acid (TCA) cycle activity even under normal physiological conditions. Consistent with this lactate-fuel hypothesis, several lines of study have also provided evidence that lactate can support energy metabolism during ischemia, which can rescue neuronal death after ischemia or under conditions of oxygen GD (Berthet et al, 2009). Recently, Rinholm et al (2011) reported that lactate can support axonal function in white matter under conditions of energy deprivation and that exogenous L-lactate can support oligodendrocyte development and myelination.…”
Section: Introductionmentioning
confidence: 71%
“…These young were subsequently found to have significantly smaller lesions in basal ganglia. In cases where the application of lactate was delayed (after 1 h of reperfusion or later) the neuroprotective effect was no longer demonstrated 21 . In human medicine however, there is very little evidence for the relationship between lactate levels and the prognosis of children following trauma.…”
Section: Discussionmentioning
confidence: 99%
“…It has been hypothesized that astrocytes may produce lactate during neuronal activation. Lactate is then oxidized by neurons to yield energy, playing a neuroprotective role after cerebral ischemia [32,33]. According to other authors, oxidation of lactate by neurons would only be possible if the glycolytic consumption of glucose or its transport were inhibited [34].…”
Section: Measurements In Glucose Deprivationmentioning
confidence: 99%